"Strategi dan Tantangan dalam Manajemen Perubahan: Studi Kasus Pengembangan Kota Percut Sei Tuan, Deli Serdang" - Putri Khairani Pratiwi; Nuri Aslami (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
Percut Sei Tuan City has great potential in developing the economic sector, infrastructure and public services to improve the quality of life of its people. However, with rapid growth also comes the challenge of managing the change. Ineffective change management can result in inefficiencies, inequality, and negative impacts on the environment and local communities. This study aims to analyze the strategies and challenges associated with change management in the context of developing the city of Percut Sei Tuan, Deli Serdang. In this study, a qualitative approach was used with the case study method. Data was collected through in-depth interviews with relevant stakeholders, such as government officials, community leaders and local entrepreneurs. In addition, documentation and policy analysis are also carried out to gain a comprehensive understanding of the context of changes that are currently taking place. The results of the study indicate that there are several important strategies in change management in the city of Percut Sei Tuan. First, a strong understanding of the city's development vision is needed to create a clear direction in planning and implementing change. Second, effective collaboration between government, society and the private sector is needed to ensure strong and sustainable support for such change. In order to overcome these challenges, this research recommends steps such as increasing stakeholder communication and participation, strengthening cooperation between sectors, allocating resources wisely, and increasing public awareness through education and campaigns. By adopting this strategy, it is hoped that the development of the city of Percut Sei Tuan can run smoothly and be successful in achieving sustainable development goals.